Conservative versus aggressive antiplatelet strategy for emergent carotid stenting during stroke thrombectomy. Issue 3 (June 2023) - Pop, Raoul; Severac, François; Hasiu, Anca; Mihoc, Dan; Mangin, Pierre H; Chibbaro, Salvatore; Simu, Mihaela; Tudor, Raluca; Gheoca, Roxana; Quenardelle, Véronique; Wolff, Valérie; Beaujeux, Rémy
Background: There is no consensus regarding optimal antiplatelet regimen for emergent carotid stenting during stroke thrombectomy. We aimed to assess the safety and efficacy of an aggressive periprocedural antiplatelet strategy focused on preserving stent patency, in comparison with conservative antiplatelet strategy consisting of aspirin monotherapy. Materials and Methods: Retrospective review of a prospectively collected database in a comprehensive stroke center, including all cases of emergent carotid stenting for tandem lesions stroke between 01.03.2012–01.06.2021. Aggressive antiplatelet strategy consisted of dual antiplatelet therapy (DAPT) with aspirin and clopidogrel loading doses, with added intravenous (IV) tirofiban if in-stent thrombosis was observed during thrombectomy. Clinical and radiological outcomes were compared between conservative and aggressive antiplatelet treatment groups using inverse probability of treatment weighting (IPTW) analysis based on propensity scores. Results: We included 132 cases (76.5% atheroma, 22.7% dissection, 0.7% carotid web). Forty-five patients (34%) cases received conservative antiplatelet therapy. The remaining 87 (65.9%) received aggressive antiplatelet therapy: 66 (75.8%) treated with DAPT, 21 (24.1%) with DAPT and tirofiban. Periprocedural heparin was avoided in all cases. In adjusted analysis of the weighted samples, aggressive antiplatelet strategy was associated with improved carotid stent patency (aOR 0.23, 95% CI 0.07–0.80, p  = 0.021), higher proportion of moderate clinical outcome (mRS ≤ 3, aOR 2.72, 95% CI 1.01–7.30, p  = 0.04), with no significant differences in mortality and hemorrhagic transformation (HT) rates. Conclusions: In this retrospective study, aggressive periprocedural antiplatelet strategy led to improved stent patency and clinical outcomes, without increased HT. Further prospective randomized research is warranted to identify the optimal combination of antiplatelet agents for emergent carotid stenting in the setting of acute stroke.